Trend analysis of lung cancer incidence and mortality in Grande Cuiabá, Mato Grosso, Brazil, 2000 to 2016 - Juliana Fernandes Cabral; Romero dos Santos Caló; Flávio de Macêdo Evangelista; Juliana Benevenuto Reis; Julio Fernando Pinto Oliveira; Fernanda Cristina da Silva de Lima; Noemi Dreyer Galvão; Ageo Mário Cândido da Silva (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT: Objective: To analyses lung cancer incidence and mortality trends to gender and age group in Grande Cuiabá between 2000 to 2016. Methods: Study of times series applying incidence data from the Population-Based Cancer Registry of Cuiabá, and mortality data from Mortality Information System. Annual Percentage Change and the Average Annual Percentage Change were calculated in the incidence and mortality rate through the Joinpoint regression. Results: It was observed between men a decrease of -2,2% in the overall incidence of lung cancer during the term of 2000-2016 and by age range: 40 to 49 years (-4,2%), 60 to 69 years (-2,0%) and 70 to 79 years (-9,4%), in this last age group it was between 2000-2009. The general mortality was stable on historical series, nonetheless, a decline between men of 50 to 59 years (-3,5%) among 2006 to 2016 and of 70 to 79 years among 2002-20011 (-6,3%) were observed. The incidence trends among female individuals maintained stable whereas the overall mortality trends had an increase of 7,2% between 2000-2012 and decrease of -34,1% between 2012-2016. Amid women from 50 to 79 years, there was a raise, ranging from 3,5% to 3,9% between 2000-2016. Conclusions: There is an evident disparity between the trends analysis of incidence and mortality of lung cancer among men and women, that can be explained by changes in smoking over time, for example, the adherence or not of the smoking withdraw program besides social, cultural, economics differences and even biological.